1977
DOI: 10.1038/bjc.1977.247
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement by cytotoxic agents of artificial pulmonary metastasis

Abstract: Summary.-The formation of lung colonies by i.v. injected Lewis lung-tumour cells in syngeneic recipients was greatly enhanced by prior treatment of the mice with cyclophosphamide. The lung-cloning efficiency was linearly related to cyclophosphamide dose and the optimum time of treatment was 2-4 days before the injection of tumour cells. The resulting lung colonies had a similar size distribution to colonies in untreated recipients. Bleomycin, local thoracic irradiation and wholebody irradiation were much less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…It may therefore be that the condition of the lung which makes it more susceptible to Cy lung damage also makes it more susceptible to tumour implantation. Strain differences make such conclusions speculative at present, since in C57 mice the optinmal time for Cy enhancement of lung colonies is 2-4 days (Steel & Adams, 1977). However, these particular mice may have delayed development of lung changes, since their median survivals following lung irradiation were between 200 and 310 days, whereas in CBA mice the medians ranged from 95 to 130 days, which are similar to the median survivals reported by other investigators (Steel et al, 1979).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It may therefore be that the condition of the lung which makes it more susceptible to Cy lung damage also makes it more susceptible to tumour implantation. Strain differences make such conclusions speculative at present, since in C57 mice the optinmal time for Cy enhancement of lung colonies is 2-4 days (Steel & Adams, 1977). However, these particular mice may have delayed development of lung changes, since their median survivals following lung irradiation were between 200 and 310 days, whereas in CBA mice the medians ranged from 95 to 130 days, which are similar to the median survivals reported by other investigators (Steel et al, 1979).…”
Section: Discussionsupporting
confidence: 77%
“…injections of tumour cells (van Putten et. al., 1975;Carmel & Brown, 1977;Steel & Adams, 1977). In the C3H mice, enhancement was optimal when the drug was given 24 h before the tumour cells (Carmel & Brown, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…When counting colonies, care was also taken to distinguish between tumour and host-derived colonies . Lung-colony assay The lung colony assay has been described in detail for the LL tumour by Steel & Adams (1977). In this study all implants consisted of viable cells plus 106 heavily irradiated feeder cells and 106 15 gum diameter plastic microspheres.…”
Section: Methodsmentioning
confidence: 99%
“…Various authors (Van Putten et al, 1975;Steel & Adams, 1977) showed that cyclophosphamide pre-treatment could increase, by more than 1000-lold, the number of lung colonics in a mouse mammary tumour model. This effect was related to drug cytotoxicity against host tissue .…”
Section: Discussionmentioning
confidence: 99%